Expression of regulatory dendritic cell-related cytokines in cattle experimentally infected with Trypanosoma evansi - MEKATA, Hirohisa (J Vet Med Sci, 2015)
Trypanosoma evansi causes wasting disease in many livestock. T. evansi infection gives rise to inflammatory immune responses, which contribute to the development of inflammation-associated tissue injury. We previously reported that regulatory dendritic cells (DCs), which act as potential regulators of inflammation, were activated in infected mice and transfer of regulatory DCs to infected mice prolonged their survival. However, the kinetics of regulatory DCs in cattle, which are natural hosts of T. evansi, remained unclear. In this study, we report that the expressions of CCL8 and IL-10, which promote the development of regulatory DCs, were up-regulated in cattle experimentally infected with T. evansi. This finding is potentially useful for studying the control strategy of T. evansi infection in cattle.